A phase 2 randomized, double-blind, placebo-controlled, proof-of-concept study of oral seletalisib in primary Sjögren's syndrome. (19th September 2020) - Juarez, Maria; Diaz, Nieves; Johnston, Geoffrey I; Nayar, Saba; Payne, Andrew; Helmer, Eric; Cain, Dionne; Williams, Paulette; Devauchelle-Pensec, Valerie; Fisher, Benjamin A; Giacomelli, Roberto; Gottenberg, Jacques-Eric; et al.
Abstract: Objectives: This phase 2 proof-of-concept study (NCT02610543) assessed efficacy, safety and effects on salivary gland inflammation of seletalisib, a potent and selective PI3Kδ inhibitor, in patients with moderate-to-severe primary Sjögren's syndrome (PSS). Methods: Adults with PSS were randomized 1:1 to seletalisib 45 mg/day or placebo, in addition to current PSS therapy. Primary end points were safety and tolerability and change from baseline in EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) score at week 12. Secondary end points included change from baseline at week 12 in EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) score and histological features in salivary gland biopsies. Results: Twenty-seven patients were randomized (seletalisib n = 13, placebo n = 14); 20 completed the study. Enrolment challenges led to early study termination with loss of statistical power (36% vs 80% planned). Nonetheless, a trend for improvement in ESSDAI and ESSPRI [difference vs placebo: –2.59 (95% CI: –7.30, 2.11; P =0.266) and –1.55 (95% CI: –3.39, 0.28), respectively] was observed at week 12. No significant changes were seen in saliva and tear flow. Serious adverse events (AEs) were reported in 3/13 of patients receiving seletalisib vs 1/14 for placebo and 5/13 vs 1/14 discontinued due to AEs, respectively. Serum IgM and IgG concentrations decreased in the seletalisib group vs placebo. Seletalisib demonstrated efficacy in reducing size and organisation of salivary gland inflammatory foci and in target engagement, thus reducing PI3K-mTOR signalling compared with placebo. Conclusion: Despite enrolment challenges, seletalisib demonstrated a trend towards clinical improvement in patients with PSS. Histological analyses demonstrated encouraging effects of seletalisib on salivary gland inflammation and organisation. Trial registration: https://clinicaltrials.gov, NCT02610543.